Analisis Wacana Digital Tindak Tutur dalam Konten "Ngobrolin Goblok secara Komprehensif" pada Kanal YouTube @Felix Siauw - Ramadhani, Hilmy Yavi; Nurhaqiqi, Hanna (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines digital discourse practices in Felix Siauw’s YouTube content titled “Ngobrolin Goblok secara Komprehensif” using Rodney H. Jones’ model of digital discourse analysis. The research focuses on text, context, action interaction, illocutionary speech acts, as well as the ideology and power embedded within the content and audience responses. The analysis reveals that Felix Siauw employs a communicative strategy that is polite, objective, and educational through assertive, directive, and expressive speech acts. Audience responses demonstrate appreciation, social criticism, and reflection on dependency phenomena, functioning as both educational and persuasive mediums. From the perspective of ideology and power, Felix reinforces his authority as a public figure by directing audiences toward critical, rational, and fair attitudes. This study highlights that digital discourse is not merely a space for expression but also an arena for shaping public opinion and collective awareness in the new media era.